Direct, immunological and molecular techniques for a fasciolosis survey in a rural area of San Luis, Argentina - Carnevale, Silvana (2013)
Fil: Carnevale, Silvana. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas; Argentina.